Ethnic group differences in impacts of free bus passes in England: A national study. (December 2018) - Patterson, Richard; Webb, Elizabeth; Mindell, Jennifer S.; Millett, Christopher; Laverty, Anthony A.
Abstract: Background: A pass permitting free bus travel for older people (aged ≥60 years) in England was introduced in 2006. There has been no examination of whether this scheme has differential effects across ethnic groups. We examined whether Black and South Asian participants were more likely to hold a bus pass and have higher associated levels of active travel than White participants. Methods: Data come from the National Travel Survey, a nationally representative sample of the travel patterns of households in England. Using cross-sectional data from 33, 344 participants eligible for a bus pass 2006–2014, we investigated ethnic differences in bus pass uptake and associations with bus use, active travel and walking ≥3 times per week. Results: Black participants were more likely to hold a bus pass (84%) than South Asian or White participants (74% and 75% respectively). Black participants accumulated 56% of their active travel as part of bus journeys, compared with 29% in White and 44% in South Asian participants. Bus pass possession was associated with increased odds of bus-related active travel in all ethnic groups. Conclusions: These findings suggest that the free bus pass scheme in England is associated with higher levels of active travel and that these may be greater among minority ethnic groups. Removing financial barriers to active travel could produce important health benefits particularly among ethnic minority groups, who have low levels of leisure-based physical activity. Highlights: A free bus pass scheme was associated with higher active travel among older people. Larger associations were seen in minority ethnic groups. This study reinforces the view that removing barriers to active travel can increase its use.